A systematic literature review of the semantic-rich learning environments - hamidreza rostami; shaban elahi; Alireza Hassanzadeh; Ali Moeini (International Journal of Digital Content Management, 2021)
By presenting the possibility of automatic reasoning by machines, semantic technology provides a new method for managing data and utilizing artificial intelligence based on formal and explicit patterns; emergence of these technologies in e-learning has enabled the development of next-generation learning and has created semantic-rich learning environments; So that, some researchers refer to this phenomenon as the next big wave in educational technologies. Despite the undeniable importance of this phenomenon and the many studies that have been done on semantic-rich learning environments, there is no combined knowledge that can demonstrate the evolved nature of these environments and related theories. the research, with the aim of extracting repetitive themes in the field of semantic-rich learning and expressing the basic opportunities and challenges in this field, systematically reviews the articles published in the WOS database, during the years 2000 to 2020 using the paradigm funnel technique; and has used Nvivo software in document analysis and theme extraction.